2018
DOI: 10.1080/00140139.2018.1427805
|View full text |Cite
|
Sign up to set email alerts
|

Allocating less attention to central vision during vection is correlated with less motion sickness

Abstract: Visually induced motion sickness (VIMS) is a common discomfort response associated with vection-provoking stimuli. It has been suggested that susceptibility to VIMS depends on the ability to regulate visual performance during vection. To test this, 29 participants, with VIMS susceptibility assessed by Motion Sickness Susceptibility Questionnaire, were recruited to undergo three series of sustained attention to response tests (SARTs) while watching dot pattern stimuli known to provoke roll-vection. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Conceivably, such changes might attract more of the observer's attention to their visual field, and result in greater weightings being assigned to visual (relative to nonvisual) inputs/stimulation. Consistent with this notion, several attentional effects have previously been reported for vection (e.g., Kitazaki and Sato, 2003;Seno et al, 2011b;Wei et al, 2018). The importance of wide-field visual stimulation could be tested if an observer performed a rapid-serial-visual-presentation (RSVP) task in central vision (which would concentrate their attention in central vision) before inducing vection (i.e., instead of presenting wide-field visual changes as in the present experiments).…”
Section: Effects On Vection Of Priming With Different Dynamic Visual ...supporting
confidence: 71%
“…Conceivably, such changes might attract more of the observer's attention to their visual field, and result in greater weightings being assigned to visual (relative to nonvisual) inputs/stimulation. Consistent with this notion, several attentional effects have previously been reported for vection (e.g., Kitazaki and Sato, 2003;Seno et al, 2011b;Wei et al, 2018). The importance of wide-field visual stimulation could be tested if an observer performed a rapid-serial-visual-presentation (RSVP) task in central vision (which would concentrate their attention in central vision) before inducing vection (i.e., instead of presenting wide-field visual changes as in the present experiments).…”
Section: Effects On Vection Of Priming With Different Dynamic Visual ...supporting
confidence: 71%
“…Souchet et al (2021) conducted a literature review of papers related to VR and cognitive load and suggest that cognitive load can be affected by cybersickness, but they do not suggest a specific relationship. Wei et al, 2018 showed that participants who were less susceptible to visually-induced motion sickness (VIMS, which includes cybersickness and simulator sickness) performed better at a task and posited the reallocation of attention during vection (i.e., perceived illusory self-motion) as a possible explanation. Varmaghani et al (2021) speculated about the reduction of spatial ability and attention and those factors' impact on cybersickness, but found no significant correlations between cognitive performance and cybersickness.…”
Section: Tasks Workload and Cybersicknessmentioning
confidence: 99%
“…Selection of candidates to minimize the risk has always been the preferred solution, nevertheless training procedures have also been investigated throughout the space program. Allocating less attention to the central field during visual motion stimulation has been recently found to be associated with more stable vection and higher resistance to motion sickness ( Wei et al, 2018 ). Virtual reality application designers may use this finding to strengthen and stabilize vection, while reducing the risk of visually induced motion sickness.…”
Section: Vestibular Defects and Motion Sicknessmentioning
confidence: 99%